EFEITO DO CONSUMO DA SEMENTE DE LINHAÇA INTEGRAL OU MOÍDA NA GLICEMIA DE PESSOAS COM DIABETES MELLITUS TIPO 2 - Barcelos, Laurena de Quevedo (2024)
The Type 2 Diabetes Mellitus (T2DM) is a chronic disease primarily characterized by hyperglycemia. Flaxseed, a functional food rich in soluble and insoluble fiber, has been shown to help control blood glucose levels, making it a valuable adjunct in the prevention and treatment of T2DM. The literature has explored various forms of flaxseed consumption, including whole, ground, oil, and as an ingredient in other foods, and their effects on glycemic response. However, the glycemic response to consuming whole or ground flaxseed added to a portion of French bread has not yet been investigated. To evaluate the effect of consuming a portion of French bread with whole or ground flaxseed on glycemic response in individuals with Type 2 Diabetes Mellitus. A randomized crossover clinical trial was conducted at the Biosciences Laboratory of a private university in central RS, after approval by the Research Ethics Committee under opinion number 5.747.049, with all participants signing an informed consent form. Individuals with T2DM were divided into three groups for the random consumption of bread: French bread without flaxseed (control bread), French bread with 30g of whole flaxseed, and French bread with 30g of ground flaxseed. The design was crossover with a 7-day washout period. Capillary glucose levels were monitored fasting and at 15, 30, 60, 90, and 120 minutes after bread ingestion, while plasma glucose and insulin levels were measured fasting and at the 60-minute glycemic peak. Additionally, sociodemographic, clinical (medication use, duration of T2DM, bowel habits, sleep, and physical activity), nutritional status (anthropometric assessment, blood tests), and pre-intervention dietary intake data were collected using a 24-hour food recall. Data were analyzed using the R statistical software, through Shapiro-Wilk normality tests, one-way ANOVA with Tukey post-hoc or Kruskal Wallis test. Analyses had a significance level of 5%. Sixteen individuals with T2DM participated in the study. Most were women (56%), with a mean age of 60.4 years, uncontrolled glycemia (HbA1c 8.2%), T2DM duration >10 years, using oral hypoglycemic agents, no insulin therapy, 75% practicing physical activity, and 44% overweight according to BMI. Although no significant differences were observed between the breads (p=0.91), the glycemic response was 26% lower after consuming bread with whole flaxseed and 15% lower with ground flaxseed compared to the control bread, and there was a lower insulin response (p = 0.98) and total AUC curve (p = 0.3). The results indicate a potential for flaxseed in glycemic control, and a trend suggesting that whole flaxseed may be more effective than ground flaxseed. However, further investigation is needed to confirm these effects and expand them to a larger population.